Images of the machined surface in evaluation of the efficiency of a micro-smoothing process - Zawada-Tomkiewicz, Anna (Strojniški vestnik, 2019)
The micro-smoothing in this paper concerns belt-grinding operations in two varieties that differ in the use of axial oscillations. The method relies on the continuous slow introduction of the finishing film in the working zone. The film is applied to the rotating workpiece with a defined pressure and axial oscillation. The quality of the machined surface is evaluated as a function of the finishing time. A model of the belt-grinding efficiency was developed taking into account the machined surface quality. In a monitoring system, an image of the machined surface was applied, decomposed into ten sub-images, which in turn were described by the energy parameter. The decrease of image energy was modelled, and the efficiency of the micro-smoothing process was evaluated, which in turn enabled the estimation of the finishing time. The results confirmed the correctness of the proposed methodology in the analysis of the finishing time of the belt-grinding operations.
Keywords: aksialne oscilacije; belt grinding; image processing; machining; micro-smoothing; mikro-obdelava; odrezavanje; procesiranje slik; super finiš; wavelet analysis; wavelet transformacija